1994
DOI: 10.2307/2137879
|View full text |Cite
|
Sign up to set email alerts
|

Women's and Health-Care Providers' Views of Maternal Practices and Services in Rural Nigeria

Abstract: Maternal mortality and morbidity estimates in Nigeria continue to be dramatically high largely because maternal services, especially in rural areas, are often deficient and inappropriate to women's situations. The Safe Motherhood Project in Zone A examined the pregnancy-related knowledge, attitudes, and practices of community members, and women's use of community maternal health services. Focus-group discussions and interviews confirmed a number of recent findings by other studies; they also documented extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 3 publications
0
46
0
Order By: Relevance
“…Extant literature revealed a few studies in Nigeria based on single maternity units that address women’s concerns about maternal health care services [1820]. The major strength of this study is its nation-wide focus with women in four geo-political zones and from different socio-cultural backgrounds being provided the opportunity to offer their views in a value-free manner.…”
Section: Discussionmentioning
confidence: 99%
“…Extant literature revealed a few studies in Nigeria based on single maternity units that address women’s concerns about maternal health care services [1820]. The major strength of this study is its nation-wide focus with women in four geo-political zones and from different socio-cultural backgrounds being provided the opportunity to offer their views in a value-free manner.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study in rural Tanzania, Leonard et al concluded that households collect information related to clinicians and facilities in their area through informal social interactions with their community [33]. Other research has pointed to the importance of peer advice and social networks on decisions on use of contraception, adherence to exclusive breastfeeding, and decisions to request a Caesarian section in low-and middle-income countries [34][35][36][37]. This finding is also consistent with the literature on trust and confidence in the health system, in which community interactions are a key source of information about the ability of the health system to meet individuals' needs [14,15,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…In a hospital study in Southeastern Nigeria, Dim and Onah [12] reported that 40.4 % of the pregnant women registered with the antenatal unit were anemic (hemoglobin [Hb] <11.0 g/dl). Okafor and Rizzuto had earlier warned that hospital estimates of any pregnancy-related problem are often an under-estimation of the true prevalence given that most women deliver outside the health facilities in Nigeria [13]. …”
Section: Introductionmentioning
confidence: 99%